Pemberdayaan Koperasi Serba Usaha di Kecamatan Tampaksiring Melalui Penguatan Financial Literacy - Dewi, Luh Gede Krisna; Ariyanto, Dodik; Penindra, I Made Dwi Budiana; Aksari, Ni Made Asti (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The Banjar Malet Multi-Business Cooperative in Manukaya Village is one of the cooperatives that has the potential to increase community empowerment around the Tampaksiring Gianyar District. This cooperative has great potential with 276 members, but still requires improvements in governance and human resource capabilities, especially regarding financial literacy, credit analysis, and the use of information technology in cooperative operations. The aim of this Community Service is to accelerate the spread of science and technology to the community, especially increasing financial literacy, cooperative management, and the use of information technology in cooperative management. The method of service activities is carried out through socialization, training, application of technology and mentoring, as well as evaluation for program sustainability. The results of the activity show that there is an increase in cooperative managers' understanding of financial literacy, analysis of credit provision, and the application of technology in the form of increased knowledge of using Excel in preparing cooperative reports. At the evaluation stage, it was discovered that this Community Service activity was successful in improving the human resource capabilities of cooperative managers and improving the quality of cooperative governance for the better.